Edu-manga. Helen Adams Keller - Sato, Sachiko; Yagi, Rie; Nakrosis, Dan (Digital Manga Pub., 2005)
Presents a graphic novel depicting the life of Helen Keller, who became both deaf and blind as an infant, and her teacher Anne Sullivan.